TINJAUAN YURIDIS TERHADAP TINDAK PIDANA KELALAIAN DALAM PELAKSANAAN TUGAS PADA TERBITNYA IZIN PENGEDAR DALAM NEGERI TUMBUHAN LIAR YANG TIDAK DILINDUNGI (Studi Putusan Nomor 36/Pid.B/Lh/2022/Pn Tjk) - Recca Ayu Hapsari; Indah Satria; Muhammad Satria Akbari (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
The purpose of this study was to find out the reasons why the perpetrators committed the criminal act of coercing permits for domestic distribution of wild plants that were not protected based on Decree No. 36/Pid.B/LH/2022/PN Tjk, Discussing legal issues . Consequences in criminal cases of enforcing permits for domestic distribution of wild plants that are not protected (Review of Decision No. 36/Pid.B/LH/2022/PN Tjk). The research method uses a prescriptive approach. The factors that prompted the perpetrators to commit the criminal act of implementing permits for the domestic distribution of wild plants that were not protected in Decision No. 36/Pid.B/LH/2022/ PN.Tjk based on factors and perpetrators did not consider it. Explaining the consequences of negligent actions, the perpetrator does not know that his actions can lead to unlawful consequences. The perpetrator's negligence in taking legal precautions means that the perpetrator did not exercise due care, intention, skill, prevention or wisdom in carrying out the act. This is the basis for perpetrators to commit crimes without issuing permits according to law. The legal consequence arising from the defendant's actions is a violation of the fourth alternative lawsuit Article 106 of the Law of the Republic of Indonesia Number 18 of 2013 concerning Prevention and Elimination of Forest Damage. The requirements for negligence in carrying out tasks based on Article 28 letter H are fulfilled in accordance with the law. The defendant's actions violated the fourth alternative charge of Article 106 of the Law of the Republic of Indonesia No. 18 of 2013 concerning Prevention and Elimination of Forest Damage. Therefore, as a result of the defendant's actions, the panel of judges sentenced the defendant to seven months' imprisonment and replaced him with a fine of Rp. one month.